Paper Patients: When Documents Stand in for Patients (Medicine Anthropology Theory, 2022)
This article analyses a seemingly mundane feature of a mental health centre for immigrants and refugees in Paris: the documents used by budding therapists undertaking their apprenticeships. Supervisors developed these documents in order to train therapist apprentices to learn the explanatory models of patients, identify the voice of patients, and incorporate medical anthropology into their therapeutic practice. The documents were central to the experiences of therapist apprentices because they occupied most of their time and were a substitute for supervision and patient contact. Documents disciplined the speech of therapist apprentices and focused their attention on specific aspects of patients’ histories. Therapist apprentices found these documents and documentary practices to be problematic because they reduced patients’ complex migration and medical histories to a series of tick boxes and short answers. These documents generated new forms of uncertainty among therapist apprentices about how to present clinical information about patients to their supervisors. This article is part of a larger study that considers mental health services for immigrants and refugees as communities of practice in which therapist apprentices learned to develop clinical and caring skills for vulnerable patient populations. By drawing on and contributing to scholarship on apprenticeship, uncertainty, documents, and bureaucracy, this article demonstrates how bureaucratic processes and documentary artefacts may generate unnecessary forms of uncertainty and hinder participation in communities of practice.